2022
DOI: 10.3389/fonc.2022.957404
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of TP53 and SPOP mutations and their impact on survival in metastatic prostate cancer

Abstract: BackgroundAlthough TP53 and SPOP are frequently mutated in metastatic prostate cancer (PCa), their prognostic value is ambiguous, and large sample studies are lacking, especially when they co-occur with other genetic alterations.MethodsGenomic data and patients’ clinical characteristics in PCa were downloaded from the cBioPortal database. We extensively analyzed other gene alterations in different mutation status of TP53 and SPOP. We further subdivided TP53 and SPOP mutation into subgroups based on different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the current study, elevated SETD2 expression was significantly associated with a poorer prognosis, indicating its significance as a potential biomarker for disease aggressiveness and lethality. Mutations in the SETD2 gene were reported in many tumors, leading to more aggressive biological behavior of the tumor, including features related to its plasticity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, elevated SETD2 expression was significantly associated with a poorer prognosis, indicating its significance as a potential biomarker for disease aggressiveness and lethality. Mutations in the SETD2 gene were reported in many tumors, leading to more aggressive biological behavior of the tumor, including features related to its plasticity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The high MRS subgroup presented a higher mutation frequency of TP53 (31%), and the low MRS subgroup tended to have a higher proportion of SPOP mutations (12%). Studies have reported a mutually exclusive relationship between TP53 and SPOP mutations, both of which are independent prognostic markers for CRPC [52,53]. For example, alterations in TP53 were associated with a decreased dependence of the tumor on AR signaling, which was associated with ARSI, whereas the highest levels of AR activity were found in the SPOP mutant subtype, indicating a good response to androgen receptor signaling inhibitor (ARSI) [54].…”
Section: Discussionmentioning
confidence: 99%